Tailoring bismuth-based nanoparticles for enhanced radiosensitivity in cancer therapy. Issue 23 (1st June 2022) - Wen, Shumin; Ovais, Muhammad; Li, Xiaoyan; Ren, Jiayu; Liu, Tao; Wang, Ziyao; Cai, Rong; Chen, Chunying
Abstract : In this review, the latest researches of bismuth-based nanomaterials (Bi-based NPs) as radio-sensitizers are thoroughly elucidated including both advantages to strengthen and disadvantages to improve, providing a useful guidance for the future clinical application. Abstract : Achieving a complete response to cancer treatment is a severe challenge, and has puzzled humans for a long time. Fortunately, radiotherapy (RT) gives rise to a common clinical treatment method, during which the usage of radiosensitizers is essential. Among preclinical radiosensitizers, bismuth-based nanoparticles (Bi-based NPs) are widely explored in cancer diagnosis and treatment, because they share favourable properties, such as low toxicity, strong X-ray absorption and facile preparation. However, pure Bi alone cannot achieve both efficient and safe RT outcomes, mainly due to poor targeting of tumor sites, long retention-induced systemic toxicity and immune resistance. This work provides an overview of recent advances and developments in Bi-based NPs that are tailored to enhance radiosensitivity. For the fabrication process, surface modification of Bi-based NPs is essential to achieve tumor-targeted delivery and penetration. Moreover, the incorporation of other elements, such as Fe ions, can increase diagnostic accuracy with optimal theranostic efficacy. Meanwhile, the structure–activity relationship can also be manipulated to maximize the chemotherapeutic drug loading capability of Bi-based NPs, to enhance X-ray attenuation by means of a large surface area or to achieve safer metabolic routes with rapid clearance from the human body. In addition, Bi-based NPs exhibit synergistic antitumor potential when combined with diverse therapies, such as photothermal therapy (PTT) and high-intensity focused ultrasound (HIFU). To summarize, the latest research on Bi-based NPs as radiosensitizers is described in the review, including both their advantages and disadvantages for improving treatment, thus providing a useful guide for future clinical application.